Il supporto alla «leadership» diffusa in relazione agli esiti delle rilevazioni esterne - Giovanni Moretti (LED Edizioni Universitarie, 2014)
The Weight of Quantitative Studies in the Exercising of Leadership in the School Field The article presents the importance of leadership in educational policies and shows the weight of the spreading of outcomes of both national and international comparative assessments on leadership geared to promoting improvement processes. The contribution examines certain critical aspects of the Italian context that seem to limit the exercising of leadership in the school field: the use of survey results that make policymakers less accountable; the delusionary and reassuring use made of survey results for schools, teachers and school heads; the application of many external evaluation methods in the face of an evident disengagement with regard to the improvement of didactic organization and the qualification of learning processes. The article also indicates the spheres in which survey results are strategic in order to improve teaching and to qualify learning processes. Finally, the importance that leadership can have in the school field for promoting a culture of data and evaluation is affirmed.